Hakol Kol Yaakov : The Joel Roth Jubilee Volume - Harris, Robert A.,; Milgram, Jonathan S., (The Brill Reference Library of Judaism ;, 2021)
Hakol Kol Yaakov: The Joel Roth Jubilee Volume contains twenty articles dedicated to Rabbi Joel Roth, written by colleagues and students. Some are academic articles in the general area of Talmud and Rabbinics, while others are rabbinic responsa that treat an issue of contemporary Jewish law. In his career, Joel Roth has been known as a scholar and teacher of Talmud par excellence, and, without question, as the preeminent decisor of Jewish law for the Conservative movement of his generation. In the meticulous style and approach of the Talmud scholarship of his generation, Roth painstakingly and precisely assayed the vast array of rabbinic legal sources, and proceeded to apply these in pedagogy, in scholarship and particularly in the production of contemporary legal responsa. The articles in this volume reflect the unique and integrated voice and vision that Joel Roth has brought to the American Jewish community.